Factors Influencing Oncology Nurses Discussing Cannabis Use with Patients Experiencing Chemotherapy-Induced Nausea - Xiao, Tianhao (Université d'Ottawa / University of Ottawa, 2022)
Background: Cannabis has been legalized in Canada since October 2018 and shown to be effective for chemotherapy-induced nausea (CIN). Purpose: Guided by the Ottawa Model of Research use, the aim was to determine factors influencing oncology nurses discussing cannabis use with patients experiencing CIN. Part I: A literature review to identify oncology nurses’ practices, knowledge, and attitude toward providing guidance on cannabis use for patients with CIN. Twelve articles were included. Results showed that health care professionals were hesitant to provide guidance for patients on using cannabis for medical purposes. But no studies specifically focus on nurses and CIN. Part II: A descriptive, cross-sectional study was conducted using survey methods. Twenty-five Canadian oncology nurses responded to the survey. Half (n=11) correctly answered the knowledge question about the effectiveness of cannabis. Most (n=18) did not feel confident providing guidance on use of cannabis for CIN. The top three barriers identified are social stigma, lack of knowledge, and lack of support in the workplace. Conclusion: Few Canadian oncology nurses discuss cannabis use for CIN. Identified barriers need to be addressed for oncology nurses to be prepared to discuss use of cannabis for CIN.
Keywords: cannabis; chemotherapy-induced nausea; oncology; nursing care; symptom management